IMPLEMENTASI METODE STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) DALAM MENINGKATKAN CRITICAL THINKING SISWA MATERI THAHARAH KELAS VII DI SMPN 14 MALANG - Alfathrina Mahendartik (VICRATINA, 2022)
Many Islamic religious education subjects use the lecture tradition, even though there is a fiqh chapter that must be implemented. Especially the taharah material which has a complex application, lessons about purification are very important when they want to do worship. This study focuses on how to improve the critical thinking of class VII students through the Student Team Achievement Divisions (STAD) learning method. This research is located at SMPN 14 Malang. The results of students in the critical thinking process in the first cycle are 22% and the second cycle is 90%. The difference in this cycle lies in the students' efforts to improve their scores in order to reach the KKM, which is 75. Cycle I shows that the weight of opinion is still low, only a few students can dare to have an opinion. Cycle II is very helpful for researchers to improve the value of cycle I.